Meta-analysis of genome-wide linkage scans of attention deficit hyperactivity disorder (2008)
ABSTRACT: Genetic contribution to the development of attention deficit hyperactivity disorder (ADHD) is well established. Seven independent genome-widelinkage scans have been performed to map loci that increase the risk for ADHD. Although sig-nificant linkage signals were identified in some ofthe studies, there has been limited replications between the various independent datasets. The current study gathered the results from all sevenof the ADHD linkage scans and performed a Genome Scan Meta Analysis (GSMA) to identify the genomic region with most consistent linkage evidence across the studies. Genome-wide signifi-cant linkage (PSR¼0.00034,POR¼0.04) was identi-fied on chromosome 16 between 64 and 83 Mb. In addition there are nine other genomic regions from the GSMA showing nominal or suggestive evidence of linkage. All these linkage results maybe informative and focus the search for novel ADHD susceptibility genes.